Value of matrix‐assisted laser desorption ionization‐time of flight for routine identification of viridans group streptococci causing bloodstream infections. (17th April 2012) - López Roa, P.; Sánchez Carrillo, C.; Marín, M.; Romero, F.; Cercenado, E.; Bouza, E.
Abstract Phenotypic tests do not always unequivocally identify some species of viridans group streptococci (VGS). sodA sequence analysis is the most accurate method for identification, although it requires specialized personnel and has not been applied systematically in clinical microbiology laboratory routines. Matrix‐assisted laser desorption ionization‐time of flight (MALDI‐TOF) is emerging as a rapid alternative for bacterial identification. This study assesses the ability of MALDI‐TOF and the API 20 Strep system to identify VGS isolates recovered from blood cultures using sodA sequence analysis as the reference method. All clinically significant VGS isolates recovered from blood cultures between January 2007 and January 2010 were identified by sodA sequence analysis and API 20 Strep. The strains were then tested by MALDI‐TOF. Agreement between API 20 Strep/MALDI‐TOF and sodA sequence analysis was determined. We examined 124 clinical isolates. Sensitivities of API 20 strep and MALDI‐TOF for the species level identification of VGS isolates were, respectively, as follows: 60.5% and 73.4%. Sensitivities of API 20 strep and MALDI‐TOF for the group level identification were, respectively, as follows: 70% and 94.3%. The turnaround times to identify VGS isolates by sodA sequence analysis, API 20 Strep and MALDI‐TOF were 12–24, 24–48 h and 15 min, respectively. API 20 Strep cannot accurately identify all isolates of VGS. MALDI‐TOF appeared to be a rapid and reliable alternative for identification of VGS strains to group level, but was not able to discriminate closely related species of certain groups.